Sovranità operativa e ordine policentrico nell’Unione europea: una lettura “neomedievale [Operational Sovereignty and Polycentric Order in the European Union: A Neomedieval Reading] - Marsili, M. (Quaderni di Scienza Politica, 2026)
This article addresses a recurring ambiguity in the literature on the European Union: the widespread use of “neo-medieval” and polycentric metaphors to describe dispersed authority without specifying their analytical implications. While these images capture the diffusion of power beyond the nation-state, they remain largely descriptive. The paper argues that this limitation can be overcome by reconceptualising sovereignty in operational terms. It develops the concept of operational sovereignty, defined as the patterned interaction of three mechanisms: co-production of rules, shared or delegated enforcement, and structured inter-level coordination. Rather than treating sovereignty as a formal attribute of ultimate authority, the article examines how it is exercised through institutional practices across multiple levels of governance. The argument proceeds in two steps. First, it reconstructs the EU’s institutional configuration as a layered system in which authority is neither fully centralised nor purely intergovernmental. Second, it examines how this configuration operates in the cyber and hybrid domain, where regulatory capacity depends on dense public–private interdependence and technical standardisation. This empirical analysis is not illustrative but analytical: it clarifies the conditions under which dispersed authority becomes operationally effective. The article identifies both the adaptive advantages and the accountability trade-offs of such arrangements, and specifies the structural conditions under which operational sovereignty emerges. In doing so, it moves beyond metaphorical descriptions of neo-medievalism and provides a framework for analysing sovereignty in technologically mediated and polycentric political orders.